Respuesta :

Answer:

C. (x-3)^2

Step-by-step explanation:

x^2-6x+9 is a perfect square meaning that (a-b)^2=a^2-2ab+b^2

x^2-6x+9 --> a=x, b=3

so (a-b)^2=(x-3)^2

Answer:

(x-3)2

Step-by-step explanation:

First find the GCF of 6 and 9. The answer is 3. which goes in the second place.

Then you have your x in the first place. Instead of writing like this

(x-3)2(x+3)2

You can shorten it to look like this

(x-3)2

This isn't the proper way but, every time I do it like this I get them right.